BACHA POSH: PERPETUATION OF WOMEN’S OPPRESSION IN NADIA HASHIMI’S THE PEARL THAT BROKE ITS SHELL - Fairuz Zahirana Hanun; Rini Susanti Wulandari (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
The oppression of women in patriarchal societies often disguises itself as empowerment through cultural practices that appear to offer temporary freedom. One such practice is bacha posh, a tradition in Afghanistan where girls are allowed to adopt the identity of boys to access mobility, education, and social privileges. While often regarded as an act of cultural adaptation or empowerment, this tradition remains underexplored in terms of how it perpetuates gender-based oppression. This study analyzes how bacha posh is portrayed in Nadia Hashimi’s The Pearl That Broke Its Shell, revealing how the practice, though appearing liberating, ultimately sustains patriarchal control. Using qualitative textual analysis, the study applies Iris Marion Young’s Five Faces of Oppression and Jacques Derrida’s Deconstruction theory to examine how the characters in the novel experience exploitation, marginalization, powerlessness, cultural imperialism, and violence. The findings show that the advantages girls receive while performing as boys are not rooted in equality but in submission to masculine norms. When they return to their female identities, these privileges are stripped away, exposing the illusion of empowerment. The study concludes that bacha posh, rather than resisting oppression towards women, perpetuates it by allowing only conditional access to power while keeping oppressive structures intact.